Ductile design of steel structures - Bruneau, Michel; Chia-Ming Uang.; Whittaker, Andrew (New York : McGraw-Hill, 1998)
This book is about: Structural Steel; Plastic Behavior at the cross-section level; Concepts of plastic analysis; Systematic methods of plastic analysis; Applications of plastic analysis; Design of ductile braced frames; ...
Keywords: Building; Iron; Steel; Structural design; Structural design; Building, Iron and steel; Steel, Structural Ductility